Diseño de un Sistema de Generación Fotovoltaica ON-GRID para Residencia en el municipio de Buriticá, Antioquia - Moreno Moreno, Sergio Alexander (Universidad Antonio Nariño, 2023)
In this project, the search design a generation system photovoltaic ON-GRID or connected to the grid public electricity and without batteries (SGFV-OG) for a residence in the village of Higábra, municipality of Buriticá, Antioquia